Wireless, multimodal sensors for continuous measurement of pressure, temperature, and hydration of patients in wheelchair - Cho, Seokjoo; Han, Hyeonseok; Park, Hyunwoo; Lee, Sung Uk; Kim, Jae Hwan; Jeon, Sung Woo; Wang, Mengqiu; Avila, Raudel; Xi, Zhaoqian; Ko, Kabseok; Park, Minsu; Lee, Jungyup; et al. (npj Flexible Electronics, 2023)
Individuals who are unable to walk independently spend most of the day in a wheelchair. This population is at high risk for developing pressure injuries caused by sitting. However, early diagnosis and prevention of these injuries still remain challenging. Herein, we introduce battery-free, wireless, multimodal sensors and a movable system for continuous measurement of pressure, temperature, and hydration at skin interfaces. The device design includes a crack-activated pressure sensor with nanoscale encapsulations for enhanced sensitivity, a temperature sensor for measuring skin temperature, and a galvanic skin response sensor for measuring skin hydration levels. The movable system enables power harvesting, and data communication to multiple wireless devices mounted at skin-cushion interfaces of wheelchair users over full body coverage. Experimental evaluations and numerical simulations of the devices, together with clinical trials for wheelchair patients, demonstrate the feasibility and stability of the sensor system for preventing pressure injuries caused by sitting.